Automated assessment of drusen using three-dimensional spectral-domain optical coherence tomography - Iwama, Daisuke; Hangai, Masanori; Ooto, Sotaro; Sakamoto, Atsushi; Nakanishi, Hideo; Fujimura, Takashi; Domalpally, Amitha; Danis, Ronald P; Yoshimura, Nagahisa (Investigative ophthalmology & visual science, 2012)
To compare automated assessment of macular drusen delineated by the authors' originally developed algorithm on three-dimensional (3D) spectral-domain optical coherence tomography (SD-OCT) with the assessment by certified graders on color fundus photographs in nonneovascular age-related macular degeneration (AMD). Automated assessment of macular drusen was performed using raster scan by 3D OCT scans in 18 eyes with nonneovascular AMD with at least one large druse (≥125 μm) and predominantly soft indistinct drusen. Drusen was defined as the regions that have the distance between the retinal pigment epithelium and calculated Bruch's membrane lines > predefined threshold distances. The agreement was assessed on maximum drusen size and drusen area within grid between 3D SD-OCT and color fundus photographs, and false-negative and false-positive drusen at each threshold distance. There was agreement or agreement within one step in all eyes in maximum drusen size, and 15 (83.3%) of the eyes in the drusen area, except 6 pixels, regardless of threshold distances. However, the number of eyes with exact agreement in the drusen area increased when the threshold distances were smaller than 4 pixels. In the three cases with disagreement in the drusen area, false-negative drusen on 3D SD-OCT were characterized by being small in area and height. Automated assessment of drusen parameters based on the authors' algorithm on 3D SD-OCT, which was limited by the poor detection ability of small drusen, showed good agreement with the assessment by certified graders on color fundus photography in these subjects.